Deformation and Failure Characteristics and Control Technology of Surrounding Rocks in Deep High-Horizontal Stress Rock Roadways in the Wanbei Mining Area - Chen, Denghong; Yuan, Yongqiang; Ma, Li (Frontiers in Earth Science, 2022)
Taking the engineering conditions of zhujixi coal mine and Hengyuan coal mine in Wanbei mining area as the background, based on the investigation of the deformation and failure status of the surrounding rock of the two mines, the deformation and failure characteristics of the surrounding rock of deep rock roadway in Wanbei mining area are systematically studied by using the comprehensive research methods of surrounding rock mechanical parameter test, in-situ stress measurement and numerical simulation.The results show that the measured value of the intermediate principal stress is slightly less than the theoretical value, which is obviously affected by the tectonic stress. The lateral pressure coefficients of the two mines calculated according to the theory are between 1.06~1.24 and 1.18~1.24 respectively.The simulation shows that when the lateral pressure is higher than 1.5, the arrangement of drilling holes with a depth of 5-10 m and a diameter of 200-300mm can effectively transfer the stress concentration. Proposed using Ф22 L=2800mm anchor rod, row spacing 800×800 mm, specification Ф 22. For the anchor cable with length of L=6300 mm, the row spacing between anchor cables is 1600±100 mm, and the coordinated support technology of reinforcement support and grouting is added.The technology can fully mobilize the deep stable rock stratum when it is applied from the slope change point of 11 coal belt roadway in the east wing of zhujixi coal mine to the machine head chamber of 11 coal belt roadway in the west wing, and the field application is good.